Successful management of multiple pregnancies in a family with varying severity of Von Willebrand disease. (December 2018) - Harrington, Patrick; Kyle, Pippa; Cutler, Jacky; Madan, Bella
We present the obstetric history of a family of three sisters with Von Willebrand disease, managed in our centre over the course of nine successful pregnancies. The abnormalities result from inheritance of an exon 50 skipping mutation in the Von Willebrand factor gene, resulting from consanguinity. Two of the sisters were identified as having a severe phenotype with a Von Willebrand factor level of less than 5 IU/dl, with the other having a mild phenotype. Of the sisters with a severe phenotype, one had a number of prenatal complications and required early onset prophylaxis with Von Willebrand factor concentrate, whilst the other had a less complicated clinical course, only requiring Von Willebrand factor concentrate to cover labour. The sister with mild Von Willebrand disease had a rise in Von Willebrand factor levels during pregnancy and required no specialist treatment. The report highlights the markedly different clinical courses that can occur in patients with Von Willebrand disease and the different approaches to management.